Manual Book Biology Scientific Camp: Pengembangan Pendidikan Karakter Berbasis Outdoor Approach: Manual Book Biology Scientific Camp: Character Education Based On Outdoor Approach - Nasrul Hakim; Yudiyanto Yudiyanto; Halimah Sa’diah; Eka Putri Setiana (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2020)
This research aimed to develop a manual book for the implementation of a biology scientific camp to develop the character education of biology students. This book was developed with an outdoor approach. This research uses the ADDIE development model which includes the Analysis, Define, Design, Implementation and Evaluation. This research data were obtained from the results of the validation of material experts and media experts as well as the results of small group trials. The results showed the results of the material expert validation obtained a score of 92% and included in category of highly validated media expert validation obtained a score of 91% included in very valid category. The results of small group trials showed a score of 95% included in very good category, while the results of the large group trial obtained a score of 92% and included in very good category. The results showed that the manual book of Biology Scientific Camp that was developed was appropriate to be used as the development of character education based on an outdoor approach. Keywords: Character Education, Outdoor Approach. Abstrak Penelitian ini bertujuan untuk mengembangkan buku panduan (manual book) pelaksanaan kemah ilmiah biologi (biology scientific camp) sebagai upaya untuk mengembangkan pendidikan karakter mahasiswa biologi. Buku ini dikembangkan dengan pendekatan outdoor approach. Penelitian pengembangan ini menggunakan model pengembangan ADDIE yang meliputi tahap Analysis, Define, Design, Implementation dan Evaluation. Data penelitian diperoleh dari hasil validasi ahli materi dan ahli media serta hasil ujicoba kelompok kecil. Hasil penelitian menunjukkan hasil validasi ahli materi diperoleh skor 92% dan termasuk dalam kategori sangat valid validasi ahli media diperoleh skor 91% termasuk dalam kategori sangat valid. Hasil ujicoba kelompok kecil menunjukkan skor 95% termasuk dalam kategori sangat baik, sedangkan hasil ujicoba kelompok besar diperoleh skor 92% dan termasuk dalam kategori sangat baik. Hasil penelitian menunjukkan bahwa manual book Biology Scientific Camp yang dikembangkan layak digunakan sebagai pengembangan pendidikan karakter berbasis outdoor approach. Kata kunci: Pendidikan Karakter, Outdoor approach.